Analisis Kepuasan Konsumen di Cemara Asri Pasar Buah Medan - Titi Widya Enjellina Sari Sari; Sutarno Sutarno; Dewi Anggraini; Arwin; yuliana (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Cemara Asri Fruit Market is a supermarket that sells or provides various kinds of consumer needs. It has been established since May 7 2018, located at Jalan Cemara No.29-32 the beautiful fir complex, Deli Serdang, North Sumatra. This study draws on the theory from Tjiptono (2019) discussing consumer satisfaction in the fir asri fruit market with the aim of knowing consumer satisfaction when shopping at Cemara Asri Fruit Market, Medan. The author uses descriptive qualitative research methods. Sources of data used are primary and secondary data. The data collection techniques carried out by the author through interviews. Informants are subjects who understand research problems as actors and people who understand research problems. Researchers used purposive techniques in selecting informants. and the results are tested by triangulation of sources. The results of this study indicate that consumer satisfaction when shopping at Cemara Asri Fruit Market, Medan. It is still not seen from the service that is less friendly to consumers as well as the slow response of employees in handling consumer complaints. Parking facilities that can still be improved are also promotions that are less spread out.